Analisis Penerapan Sistem Informasi Akuntansi Atas Bagi Hasil Dari Penjualan Bersih (Net Sales) di PT. Tuah Globe Mining - Ardena, Dinda; Harmain, Hendra; Inayah, Nurul (Jurnal Manajemen Akuntansi (JUMSI), 2023)
In carrying out business cooperation, there is an agreement on a profit sharing system that will be obtained from profits from the sale of coal. The amount of profit sharing received must be mutually beneficial to both parties. The purpose of this study was to find out accounting information for mining operational costs and a profit sharing system from net sales of business cooperation, profit sharing procedures in financial reports that function as an accounting information system, and how sales revenue sharing is used to settle tax burdens. This type of research is field research carried out at PT. Tuah Globe Mining. The approach used in this research is descriptive-qualitative. The author will deliver the results research into a description or explanation that is easy to understand. The method that the author uses in finding data is by way of interviews, observation, and documentation. Based on the results of research conducted that the application of the system for results applied by PT. Tuah Globe Mining and PT. Kutama Mining Indonesia on coal mining business cooperation is using method revenue sharing. Profit sharing is done in a way net sales will be deducted by operating expenses invoice issurance mechanism. As for the distribution of the results will be applied in the company’s financial statements. Thur for calculating and completing the tax burden of PT. Tuah Globe Mining will be report sales in the agency’s annual SPT as stipulated in the act PPh, job creation law, and harmonization law.